Intense pain influences the cortical processing of visual stimuli projected onto the sensitized skin - Torta, DM (Pain, 2017)
Sensitization is a form of implicit learning produced by the exposure to a harmful stimulus. In humans and other mammals, sensitization following skin injury increases the responsiveness of peripheral nociceptors, and enhances the synaptic transmission of nociceptive input in the central nervous system (CNS). Here, we show that sensitization-related changes in the CNS are not restricted to nociceptive pathways and, instead, also affect other sensory modalities, especially if that modality conveys information relevant for the sensitized body part. Specifically, we show that after sensitizing the forearm using high-frequency electrical stimulation of the skin (HFS), visual stimuli projected onto the sensitized forearm elicit significantly enhanced brain responses. Whereas mechanical hyperalgesia was present both 20 and 45 minutes after HFS, the enhanced responsiveness to visual stimuli was present only 20 minutes after HFS. Taken together, our results indicate that sensitization involves both nociceptive-specific and multimodal mechanisms, having distinct time courses.